Edme Antoine Durand (1768-1835) : un bâtisseur de collections - Louise Detrez (Les Cahiers de l'École du Louvre)
His discovery of Italy in 1799 sparked the passion for collecting in Edme Antoine Durand, a wealthy merchant. Travelling around Europe and making good use of his proven ﬂair and business sense, he put together collections combining eclecticism and specialisation, quantity and quality. There were an art gallery, a cabinet of drawings, a collection of prints, antique and modern gems, a medal collection and a cabinet of arms in addition to the two renowned collections of antiquities and objets d’art commonly associated with Durand. One of them was sold in its entirety in 1825 to make up the core of the Musée Charles X, the other dispersed at public sale in 1836 after its owner’s death.